Henry A. Wallace papers - Wallace, Henry A. (Henry Agard), 1888-1965.
Correspondence, memoranda, subject files, scrapbooks, clippings, and photographs documenting Wallace's service as U.S. secretary of agriculture and as U.S. vice president. Includes material on public reaction to his trip to South America in 1943 and his speech seconding the renomination of Franklin D. Roosevelt for the presidency in 1944.
Microfilm edition of volumes. 1-84 available
Microfilm produced from originals in the Manuscript Division.
Author, editor, and statesman.
Collection material in English, with Spanish.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Roosevelt, Franklin D. -- 1882-1945.; Wallace, Henry A. -- 1888-1965 -- Public opinion; United States. -- Department of Agriculture. -- Office of the Secretary; Presidents -- United States -- Election -- 1944.; South America -- Foreign relations -- United States; United States -- Foreign relations -- South America; United States -- Politics and government -- 1933-1945.; Authors; Cabinet officers; Editors; Statesmen; Vice-Presidents -- United States